The Crime of Begging in Public Based on Article 504 Paragraph (1) of the Criminal Code - Febianti, Pepe; Nurkholim, Nurkholim (CV. Publikasi Indonesia, 2024)
The imbalance between job seekers and job recipients makes it difficult for some Indonesians to find work. This study aims to determine the handling of the crime of begging in public based on Article 504 Paragraph (1) of the Criminal Code and also to determine the termination of the crime of begging in public in connection with the Tulungagung District Court Decision Number 69/Pid.C/2022/PN. In addition, to determine the suitability of the crime of begging in public based on article 504 of the Criminal Code with article 429 of the new Criminal Code and whether the handling of the crime of begging in public is effective or not. The research method used in this study is descriptive-analytical with a normative juridical approach. The conclusion of this study is that the handling of the crime of begging in public based on Article 504 paragraph 1 of the Criminal Code associated with the Tulungagung District Court Decision Number 69/Pid.C/2022/PN Tlg has been implemented appropriately. This is manifested in Tulungagung District Court Decision Number 69/Pid.C/2022/PN Plg where the judge ruled that the perpetrators of the crime of begging in public are punishable in Article 504, article 1 (one) of the Criminal Code. So that Article 504 paragraph 1 (one) has not been effectively implemented in the community and the punishment is in accordance with applicable laws and regulations. To reduce similar crimes, the government must intervene to deal with the poverty rate in Indonesia so that the level of begging in Indonesia is reduced.